The impact of Liquidity and free float on stock returns: evidence from Bursa Malaysia - Lau, Anthony Tiong Tiing (Universiti Malaysia Sarawak (UNIMAS), 2013)
The aim of this paper is to review the impact of liquidity and free float on stock returns of Malaysian listed companies in Bursa Malaysia. In this study, liquidity is proxied by stock turnover rate, which is the ratio of turnover by volume of specific stock over total turnover by volume of the samples and free float is calculated as the ratio of free float market value over market values of specific stock. Our study makes use of cross-sectional regression framework using annual1y sample data over the period April 2003 to April 2013. We encounter that liquidity is positive related to stock return, which is opposed the prior finding in the researches that are executed by Datar, Naik and Radcliffe (1998), Chan and Faff (2005) and Chang, Faff and Hwang (2010), but in line with Ramlee and Ali (2012) finding that liquidity is significant positive related to stock return in Malaysia. The free float is found negative related to stQck return.